Social Validation as a Key Process to Participatory and Engaged Research: Learning from a Brazilian Academic Program - Harari, Teresa; Pozzebon, Marlei; Souza, Ana Clara; Dias, André Luiz Freitas; de Sousa Teodósio, Armindo dos Santos (Canadian Journal of Nonprofit and Social Economy Research / Revue canadienne de recherche sur les OSBL et l’économie sociale, 2025)
Participatory and engaged research is an approach in which the traditional boundaries between subject (the one who investigates) and object (the one being investigated) are intentionally blurredand both construct purpose and knowledge. In this type of inquiry, the researcher—alongside research participants—not only analyzes or interprets social reality but actively seeks to transform it. While this approach poses significant challenges, particularly as direct engagement with the field is often seen as a threat to research validity, this article advocates for its value as a powerful methodological strategy for scholars committed to social change. It introduces the concept of social validation, which supports the legitimate recognition of collaborative research not only within academia but also by the communities involved.